The Influence Of Parenting Styles To The Character Building Of The Youth Of Churches Members Of Bamag In Blitar City - David Victor Arthur Pualalo; Yunita Stella; Lilis Setyarini (Theological Journal Kerugma, 2022)
The concept of parenting is tested in the character building of the youth of churches members of BAMAG in Blitar City. The purpose of this study is to determine whether parenting styles influences to the character building of the youth of churches members of BAMAG in Blitar City. The technique used in this research is the quantitative method. The respondents needed are 160 youth churches that are members of BAMAG in Blitar City and the author focuses on charismatic churches that are members of BAMAG. The results of the study concluded that the hypothesis in this study, namely the tendency of the influence of parenting styles (X) to the character building of the youth of churches members of BAMAG in Blitar City (Y) is "high" is proven, because the influence of parenting styles to the character building of the youth of churches members of BAMAG in Blitar City are 75.4% in the high category.